Does syncope require rhythmic and non-rhythmic evaluation in patients with previous MI?. Issue 1 (29th July 2010) - Brembilla-Perrot, B; Suty-Selton, C; Alla, F; Zinzius, P Y; Blangy, H; Azman, B; Terrier de la Chaise, A; Louis, P; Groben, L; Djaballah, K; Selton, O; Magalhaes, S; et al.
Abstract : Background: Multiple factors, in addition to left ventricular ejection fraction (LVEF) influence the risk of mortality in coronary artery disease. The purpose of this study was to evaluate the main causes of syncope after myocardial infarction (MI) and to propose an algorithm of management. Methods: 356 patients consecutively admitted for syncope and history of MI (>1 month), without ventricular tachycardia (VT), underwent echocardiography, Holter monitoring, head-up tilt test, exercise testing, signal-averaged ECG, electrophysiological study (EPS) and evaluation of coronary status. The mean follow-up was 4±2 years. Results: Monomorphic VT, ventricular flutter or fibrillation (VF) and supraventricular tachyarrhythmia were respectively induced at EPS in 87, 63 and 39 patients; conduction disturbances were noted in 23 patients, and 57 patients had several abnormalities. Among the 144 patients with negative EPS, coronary ischaemia was identified in 37 patients, and hypervagotonia in 27 patients. All studies remain negative in 84 patients (23.6%), more frequently women (p<0.001). Four patients died suddenly during follow-up. A longer QRS duration, a lower LVEF and grade IVa, b of Lown on Holter ECG were associated with the induction of VT. LVEF<40% and VT/VF induction were predictors of cardiac mortality, VT was a predictor of sudden death, and low LVEF and advanced age were predictors of death by heart failure. Conclusion: Myocardial ischaemia, hypervagotonia, conduction abnormalities, ventricular or supraventricular tachyarrhythmias were identified in 76% of patients with syncope after MI. Several factors of syncope were found in 57 patients (16%). Non-invasive rhythmological and systematic coronary status assessment should be recommended in patients with syncope following MI.